Efficacy of pinaverium bromide in the treatment of irritable bowel syndrome: a systematic review and meta-analysis. (September 2021) - Bor, Serhat; Lehert, Philippe; Chalbaud, Adriana; Tack, Jan
Background: Spasmolytic agents are an attractive first line treatment option for irritable bowel syndrome (IBS). Pinaverium bromide (pinaverium) has antispasmodic effects on gastrointestinal smooth muscle and can relieve major IBS symptoms, but an up-to-date meta-analysis comparing the efficacy of pinaverium with placebo is lacking. The aim is to perform a systematic review and meta-analysis to assess the efficacy of pinaverium compared with placebo for IBS treatment. Methods: All placebo-controlled trials evaluating pinaverium for IBS treatment were included, up to October 2019. Treatment efficacy was evaluated by overall patient IBS symptoms. Individual symptoms were also evaluated. The effect of pinaverium versus placebo was expressed as standardized mean difference (SMD) and risk ratio (RR). Odds ratio (OR) and number needed to treat (NNT) were also calculated. Results: Eight studies were included for analysis. Pinaverium treatment had a beneficial effect on overall IBS symptom relief with a positive SMD of 0.64 [95% confidence interval (CI) 0.45–0.82, p  < 0.0001] and a positive RR of 1.75 (1.26–2.43, p  < 0.0008). No significant difference was found by publication year, gender, age, methodological quality score (MQS), or sample size. No publication bias was detected. OR was 3.43 (2.00–5.88, p  < 0.0001), and NNT was 4. Pinaverium also demonstrated a beneficial treatment effect for abdominal pain, stool change, and bloating improvement or resolution. Conclusion: Pinaverium is superior to placebo for the treatment of IBS symptoms, irrespective of patient age or gender, study publication year, sample size, or MQS. The NNT in this meta-analysis is amongst the lowest for studies and meta-analyses of antispasmodics versus placebo in IBS.